2012
DOI: 10.4236/sm.2012.21012
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Social and Personal Attitudes after Wildfires in a Rural Region of Greece

Abstract: We investigated the trust in institutions, social values and personal attitudes of individuals in a part of Greece, after a wildfire disaster. The design of the study was a cross sectional, case-control study. Data collected were trust in institutions, social and personal attitudes, type and number of losses. The results show that victims and controls have low trust in all the institutions and share similar social and personal attitudes. Controlling for other variables, victims of the wildfires were less likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…They also showed that the relationship between the earthquake and levels of social trust was dependent on past levels of social trust. However, Miller [32], Fleming et al [33], Papanikolaou et al [34] and Ahsan [35] all showed that natural disasters had negative effects or no effects on social trust. Although many studies found evidence that natural disasters influence underlying preferences, the direction of the influence varies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also showed that the relationship between the earthquake and levels of social trust was dependent on past levels of social trust. However, Miller [32], Fleming et al [33], Papanikolaou et al [34] and Ahsan [35] all showed that natural disasters had negative effects or no effects on social trust. Although many studies found evidence that natural disasters influence underlying preferences, the direction of the influence varies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is supported by the research of Kay et al (), who found that faith in government and in God exhibited a hydraulic relationship: as faith in government systems decreased, faith in God increased, and vice versa. Similarly, Papanikolaou et al () discovered that those who experienced wildfires in Greece had less trust in governmental institutions, but were more likely to trust religious bodies. In some cases, individuals may attribute some responsibility to themselves, either owing to their own behaviour or to their own personal characteristics (Hodgkinson and Stewart, ).…”
Section: Introductionmentioning
confidence: 99%
“…Disasters affect the attitudes and beliefs of those who suffer their consequences, which can have a significant bearing on emotional responses (Foa et al, ). Such attitudes, beliefs, and emotions pertain to matters such as faith in institutions of governance and cultural and social agencies (Gray and Wegner, ; Kay et al, ; Sibley and Bulbulia, ), benevolence of the world (Janoff‐Bulman, ; Solomon, Lancu, and Tyano ; Poulin and Silver, ), self‐blame and self‐worth (Hodgkinson and Stewart, ; Nygaard and Heir, ), sense of control (Ehlers and Clarke, ; Prati, Catufi, and Pietrantoni, ), relationships with other people (Papanikolaou et al, ), feelings of solidarity (Joakim, ; Hutchison, ), and opinions about the future (Solomon, Lancu, and Tyano ). Furthermore, evidence suggests that some impacts on belief systems may contribute to longer‐term emotional and psychological disorders, such as post‐traumatic stress disorder (PTSD) (Ehlers and Clarke, ; Goenjian et al, ; Dekel et al, ; Crostley, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are also examples of the negative social effects of disasters, however, emphasising the potential social dilemma. Papanikolaou et al () found that the victims of wildfires in Greece in August 2007 were less likely to appreciate mutual support. The experiences of survivors of Hurricane Katrina in New Orleans, Louisiana, US, also describe negative effects on the community (such as owing to looting) and on social trust (Miller, ).…”
Section: Social Capital and Disastersmentioning
confidence: 99%
“… First, do levels of social capital change with respect to disaster events? Existing research focuses mostly on single cases that cannot constitute a basis for generalisation (Castillo and Carter, ; Papanikolaou et al, ; Dussaillant and Guzmán, ; Yamamura, ). Hence, a more general inquiry into this question is needed.…”
Section: Introduction: the Social Side Of Disastersmentioning
confidence: 99%